PENGARUH PEMBERIAN TRICHOKOMPOS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Raliandi Nadeak; Husna Yetti; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aimed to examine the effect of litter Trichocompost corn and get the correct dosage on the growth and production at mustard.  This research has been conducted on the experimental farm of the Faculty of Agriculture, University of Riau, located at an altitude of 10 meters above sea level. This study was conducted from February - March 2014. This study was performed experimentally by using Completely Randomized Design (CRD) consisting of 6 treatments. Each treatment was repeated 3 times to obtain 18 units of the experiment, one experimental plot contained 16 plants and 3 plants samples taken from each plot. Parameters observed in this study were plant height (cm), number leave (blade), leaf area (cm2), root volume (ml), fresh weight (g) and fresh weight feasible consumption (g). Data obtained from the observations were analyzed statistically, the results of the ANOVA test followed by Ducan's New Multiple Range Test (DNMRT) at the level of 5%. The results showed trichocompost giving corn litter can improve plant growth, especially height, number leave, leaf area, root volume, fresh weight and fresh weight worth of consumption. Keywords : Trichokompos and mustard (Brassica juncea L.)